ANALYSIS OF THE IMPLEMENTATION OF GROUNDWATER TAX ON DEWATERING IN JAKARTA - Agustina, Agustina; Inayati, Inayati (Universitas Medan Area, 2020)
This article aims to analyze the implementation of groundwater tax on dewatering in DKI Jakarta Province and the factors causing the collection of groundwater tax on dewatering are not optimal in DKI Jakarta Province. The problem is focused on the ground water tax policy on dewatering in DKI Jakarta Province. To approach this problem, the theory of Merilee Grindle's about policy implementation was used. Data were collected through literature study and field study and analyzed qualitatively. Through this method, data and information obtained from field studies and literature studies were then processed to draw conclusions. This study concludes that there are interests that are affected in the implementation of groundwater tax on dewatering, especially the interests of the Regional Tax and Retribution Agency. It is related to the desired benefits of implementing the policy, namely increasing groundwater tax revenues in DKI Jakarta Province. Some factors caused the implementation of ground water tax on dewatering were not optimal are human resources that are still lacking in terms of quality and quantity, data collection and supervision have not been done well, lack of coordination between related agencies, lack of socialization and unclear implementation regulations